2019
DOI: 10.15252/embj.2018100983
|View full text |Cite
|
Sign up to set email alerts
|

The herpesviral antagonist m152 reveals differential activation of STING ‐dependent IRF and NF ‐κB signaling and STING 's dual role during MCMV infection

Abstract: Cytomegaloviruses (CMVs) are master manipulators of the host immune response. Here, we reveal that the murine CMV (MCMV) protein m152 specifically targets the type I interferon (IFN) response by binding to stimulator of interferon genes (STING), thereby delaying its trafficking to the Golgi compartment from where STING initiates type I IFN signaling. Infection with an MCMV lacking m152 induced elevated type I IFN responses and this leads to reduced viral transcript levels both in vitro and in vivo. This effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…1a, b). This observation was surprising, because in a previous in vivo study STING was reported to be involved in MCMV sensing and IFN-I induction 27,28 and mice devoid of cGAS or STING showed enhanced sensitivity to the infection with other DNA viruses, such as HSV-1 and vaccinia virus (VACV) 22,24 (Supplementary Fig. 1c, d).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…1a, b). This observation was surprising, because in a previous in vivo study STING was reported to be involved in MCMV sensing and IFN-I induction 27,28 and mice devoid of cGAS or STING showed enhanced sensitivity to the infection with other DNA viruses, such as HSV-1 and vaccinia virus (VACV) 22,24 (Supplementary Fig. 1c, d).…”
Section: Resultsmentioning
confidence: 94%
“…TLR signaling plays an important role in the control of systemic MCMV infection 15 , whereas more recently it was discovered that STING signaling is needed to induce early systemic and splenic IFN-β responses 27,28 . To analyze the relevance of the cGAS/STING axis for protection against MCMV, TLR ( Myd88 −/− Trif −/− mice ) , RLR ( Mavs −/− mice), cGAS ( Cgas −/− mice), and STING ( Tmem173 −/− mice) signaling deficient mice were infected with 5 × 10 5 plaque forming units (pfu) of MCMV Δ m157 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro data generated in MACs further suggest that they induce NK-cell recruitment and IFN-γ production via inflammasome activation during the early response (Figure 1). On the other hand, MCMV and HCMV have evolved numerous strategies to evade the IFN I response (59)(60)(61)(62). As an example, the MCMV protein M35 antagonizes IFN I induction downstream of STING and TLRs and thus ensures MCMV replication in MACs (46) ( Table 1).…”
Section: And Cytosolic Sensorsmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) is a β-herpesvirus that persists mostly asymptomatically in infected healthy human hosts throughout their life [1], with spontaneous phases of reactivation, lytic replication, and diffusion [2]. HCMV causes several clinical syndromes in people with impaired immunity, especially in individuals subject to organ transplant, HIV-infected patients, and immunologically immature fetus [3].…”
Section: Introductionmentioning
confidence: 99%